Aplikasi Sistem Informasi Geografis Untuk Pemetaan Sebaran Potensi Alam dan Pemanfaatan Lahan Hutan Lindung Sibayak II Taman Hutan Raya Bukit Barisan - Geby Rhevia; Oding Affandi; Rahmawaty Rahmawaty (Peronema Forestry Science Journal, 2014)
Geographic Information System application has been used for planning, execution and operation which have the regional base of geography. One of the application is for mapping potential lansdscape distribution. Sibayak II forest area is  one of  Taman Hutan Raya Bukit Barisan conservation area which strategic located and surrounded by lot of tourism potency, natural resources potency and  hydrological function. This study aimed to mapping the distribution of natural resources potency and type of land using. This study was conducted in April until June 2013 using interview guide and ground exploration method with Geographic Information System application and Global Positioning System. The Result of this study showed that Sibayak II forest area has many natural resources potency such as flora, fauna, bamboo and water resources which distributed almost all of the edge of the forest area.The most dominant of flora is bamboo, Altingia excelsa, Schima wallichi and pine because Sibyak II is on the edge of mountain area. The type of land using at Sibayak II forest area based on local community data and ground check were bamboo cultivations, farming land and forest exploitation area.Keywords : Taman Hutan Raya Bukit Barisan, Sibayak II reserve forest, GIS